Development water supply information system of Syarikat Air Perlis [SAP] / Nur Atikah Ithma - Ithma, Nur Atikah (2019)
Individuals rely upon water for drinking, cooking, washing, diverting squanders and household needs. Water supply framework give the adequate water of fitting quality and amount has been a standout amongst the most imperative issue in human everyday lives exercises. Water supply system consists of infrastructure that collects, treats, stored and distributes water between water sources and consumers. As to deal with the information appropriately, online framework in overseeing water supply data are required to guarantee the information are efficient. Geographical Information System open sources of is ones is mechanism in reduces the world economic crisis, formed the content for the promotion and development of free systems and open source technologies. The QGIS open sources programming utilized all through the procedures. This examination went for build up the water supply data arrangement of Syarikat Air Perlis (SAP) utilizing the GIS approach. The water tank around at the Perlis is picked as a contextual analysis. The water tank around at the Perlis is chosen as a case study. The research has customized and integrated an open source system was used for the development of an interactive and friendly geographic user interface. The research has customized and integrated an open source system was used for the development of an interactive and friendly geographic user interface. The created framework empowers clients to see and collaborate with the spatial information. The research focused on improving the efficiency and effectiveness of the decision making process and data sharing.